Unleashing E-Commerce for South Asian Integration - Kathuria, Sanjay (Washington, DC: World Bank, 2019)
This report is part of a broader work program on shaping a more positive narrative on regional integration in South Asia. It is a follow-up to a recent flagship report published by the South Asia Region of the World Bank, A Glass Half Full: The Promise of Regional Trade in South Asia. E-commerce is dramatically changing the way goods and services are transacted nationally, regionally, and globally. It facilitates international trade by reducing the cost of distance and remoteness and can be more inclusive of underrepresented groups such as women, small businesses, and rural entrepreneurs. Intraregional trade in South Asia is still below its potential, and the region lags behind other parts of the world in activating the potential benefits from e-commerce.